2015
DOI: 10.1016/j.medici.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of CD4+ and CD8+ T cells in tumor islets and stroma from patients with non-small cell lung cancer in association with COPD and smoking

Abstract: According to our data, COPD but not smoking seems to be associated with higher infiltration of CD8(+) T cells in the tumor stroma of patients with NSCLC. It allows us to hypothesize that NSCLC patients with coexisting COPD may have a more favorable outcome due to anticancer properties of stromal CD8(+) T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“…It is known that tobacco smoke stimulates the infiltration of the damaged tissue by a variety of inflammatory immune cells, including neutrophils, macrophages, CD4 + , CD8 + , and B cells and infiltration of dendritic cells and natural killer cells at smaller numbers [ 37 ]. In agreement with these data, our previous study showed a greater number of total and tumor stroma-infiltrating CD4 + and CD8 + T cells in smoking NSCLC patients compared with non-smokers [ 38 ]. Macrophages accumulate in the areas of lung destruction; therefore, their numbers are increased in the lungs of healthy smokers and individuals with COPD.…”
Section: Discussionsupporting
confidence: 87%
“…It is known that tobacco smoke stimulates the infiltration of the damaged tissue by a variety of inflammatory immune cells, including neutrophils, macrophages, CD4 + , CD8 + , and B cells and infiltration of dendritic cells and natural killer cells at smaller numbers [ 37 ]. In agreement with these data, our previous study showed a greater number of total and tumor stroma-infiltrating CD4 + and CD8 + T cells in smoking NSCLC patients compared with non-smokers [ 38 ]. Macrophages accumulate in the areas of lung destruction; therefore, their numbers are increased in the lungs of healthy smokers and individuals with COPD.…”
Section: Discussionsupporting
confidence: 87%
“…Genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) which predispose to increased susceptibility to COPD and lung cancer such as SERPIN2, HHIP, FAM13A, IREB2, CHRNA3 and CHRNA5 2, 11 . Other studies also showed that inflammatory response factors, aberrant NF-κB activation and cytokine release, and high levels of CD8+ T cells mediated the link between COPD and lung cancer 12, 13 .…”
Section: Introductionmentioning
confidence: 97%
“…CD4 + /CD8 can reflect the immune balance of an organism, if the ratio is low, it means that body immune function is decreasing and may increase tumor proliferation. Of note, a low ratio is commonly regarded as the index for severe disease or a poor prognosis (21)(22)(23). In the present study, CD3 + , CD4…”
Section: Discussionmentioning
confidence: 50%